Letter from editor (2015)
More than two decades ago we have been working steadily to providereaders and scientific community with articles on a broad range of geosciences field around the world. This achievement would not be possible without the support of the Universidad Nacional de Colombia, mainly, and partners who help bring these high-quality papers to light. One of those partners is Colciencias, a Colombian Government-owned agency that support research in our country. Currently, Colciencias is carrying out a national strategic plan for Science, Technology and Innovation in Geosciences aimed to promote and develop megaprojects in the area, provide a management tool, and create a fund with resources coming from contracts of exploration and exploitation of petroleum.This 2015-2018 plan should result in the creation of new research groups, improvement of investigation centers, recognition of researchers and the double of resources in funding for projects.  Similar strategies are carried out by the Centro de Geociencias, at the National Autonomous University of Mexico. Their primary objective is to gather the experience of their academicians to produce fundamental and applied investigation under the high-quality requirements. In Venezuela, the Non-Government Organization Fundación Geoparques de Venezuela, under the motto "Geosciences for Human Development", promotes research and divulgation of earth sciences with communities as the head axis. Just these examples but in several countries of Latin America Government or Non-Government Entities work for the development of Geosciences. Our call is for regional collaboration optimizing resources, promotion of open journal publications, no isolated academic communities, etcetera. On the other hand, find available our newest volume with a selection of ten works of the best quality in different subjects of the Earth Sciences. The first of them is a complete map of the seismotectonic and geologic hazards in Iran evaluated using seismicity records, structural trends, tectonic settings, fault ruptures and neotectonics activities in the country. From Colombia, the second manuscript is an approaching to the skarn and formation of the Ti-clinohumite from its occurrence and petrologic significances. From China, but also in Petrology subject, a paper presents geochemistry and petrography of the amphiboles and plagioclase from Fenghuangshan granodiorite. Combining with the barometry and thermometry analysis, the author estimates the conditions of the Fenghuangshan magmatic rocks and explains the origin of the magma. Moreover, evaluate the deeper exploration of copper mineralization prospecting potential.In applied geophysics, a paper coming from Jordan provides information about integration of data obtained from geophysical methods, GIS and the previous works and literature review of geology in southwestern Jordan.About geomorphology, it is presented an altimetric and hypsometric analysis, with a longitudinal profile and geomorphological studies, for soil and water conservation based in the basins of Anjani and Jhiri rivers. As part of the strategies to warrant water resources, the method presented in next work is accomplished to be more efficient and cheaper to estimate runoff in a case based in Tamilnadu District, in India. Related to climatic change, one of the authors investigated the correlation of some climatic indicators with precipitation and discharge of Madarsoo (Iran) watershed. It is a meaningful study in the context of global climate change.The last block is dedicated to three works in the field of geotechnics, in areas of roads, construction of concrete piles and evaluation of polypropylene fibers for mining and civil engineering applications. We hope this articles will be useful for everyone of you. Carlos VargasEditor in Chief, Earth Sciences Research JournalMore than two decades ago we have been working steadily to provide readers and scientific community with articles on a broad range of geosciences field around the world. This achievement would not be possible without the support of the Universidad Nacional de Colombia, mainly, and partners who help bring these high-quality papers to light. One of those partners is Colciencias, a Colombian Government-owned agency that support research in our country. Currently, Colciencias is carrying out a national strategic plan for Science, Technology and Innovation in Geosciences aimed to promote and develop megaprojects in the area, provide a management tool, and create a fund with resources coming from contracts of exploration and exploitation of petroleum. This 2015-2018 plan should result in the creation of new research groups, improvement of investigation centers, recognition of researchers and the double of resources in funding for projects. Similar strategies are carried out by the Centro de Geociencias, at the National Autonomous University of Mexico. Their primary objective is to gather the experience of their academicians to produce fundamental and applied investigation under the high-quality requirements. In Venezuela, the Non-Government Organization Fundación Geoparques de Venezuela, under the motto "Geosciences for Human Development", promotes research and divulgation of earth sciences with communities as the head axis. Just these examples but in several countries of Latin America Government or Non-Government Entities work for the development of Geosciences. Our call is for regional collaboration optimizing resources, promotion of open journal publications, no isolated academic communities, etcetera. On the other hand, find available our newest volume with a selection of ten works of the best quality in different subjects of the Earth Sciences. The first of them is a complete map of the seismotectonic and geologic hazards in Iran evaluated using seismicity records, structural trends, tectonic settings, fault ruptures and neotectonics activities in the country. From Colombia, the second manuscript is an approaching to the skarn and formation of the Ti-clinohumite from its occurrence and petrologic significances. From China, but also in Petrology subject, a paper presents geochemistry and petrography of the amphiboles and plagioclase from Fenghuangshan granodiorite. Combining with the barometry and thermometry analysis, the author estimates the conditions of the Fenghuangshan magmatic rocks and explains the origin of the magma. Moreover, evaluate the deeper exploration of copper mineralization prospecting potential. In applied geophysics, a paper coming from Jordan provides information about integration of data obtained from geophysical methods, GIS and the previous works and literature review of geology in southwestern Jordan. About geomorphology, it is presented an altimetric and hypsometric analysis, with a longitudinal profile and geomorphological studies, for soil and water conservation based in the basins of Anjani and Jhiri rivers. As part of the strategies to warrant water resources, the method presented in next work is accomplished to be more efficient and cheaper to estimate runoff in a case based in Tamilnadu District, in India. Related to climatic change, one of the authors investigated the correlation of some climatic indicators with precipitation and discharge of Madarsoo (Iran) watershed. It is a meaningful study in the context of global climate change. The last block is dedicated to three works in the field of geotechnics, in areas of roads, construction of concrete piles and evaluation of polypropylene fibers for mining and civil engineering applications. We hope this articles will be useful for everyone of you. Carlos Vargas Editor in Chief, Earth Sciences Research Journal